FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEJADIAN FILARIASIS DI KABUPATEN PEKALONGAN - retnani widiyastuti (Kesmas Indonesia, 2008)
The filariasis is a main problem of health in indonesia. It is caused by the infection of filaria worm and is infected by all kinds of mosquitos. The Fillariasis spreads in almost provinces in Indonesia. Based on the territory program report and research reslut (rapid mapping) in 2000 there were 6.233 people which had chrinic case that spread over 1553 villages in 647 local government cliniscs, 26 province as an endemic area. Pekalongan regencys is the endemic Fillariasis area. The determining on the endemic area is based on microfilaria rate (Mf Rate). According to the blood result of fingers which was done in 2002 until 2006 in 7 sub district, there were 3 sub districts with rate >1% they were Wiradesa (1,4%), Tirto (1,14%) and Wonokerto (1,23%). Count of Filariasis sufferer which was reported by health department Pekalongan regency from 2002 until 2006 were 44 sufferer which spreads over in 10 subdistricts. This research was done to get to know the factors which influenced to Filariasis genesis in Pekalongan regency and the factors individual characteristics (age, sex, occupation, income, education and citizen status), environment factors (condition of vector resting places, condition of brood places, existance of reservoir, existance of cattle and ever lived with the sufferer) and behaviour (knowledge, attitude, habit of going out at night, the protection effort of mosquito bite and the efforts to eliminate mosquito nest). This study uses case control design. The sample taking technique was base on fixed disease sampling. It also used the analysis unvariate, bivariate and multivariate. The research result showed that the factors whisch influenced to Fillariasis genesis were the unwell attitude (OR=11,602 with 95% Cl = 1,2020 - 111,962) and not doing the elimination mosquitos nest (OR = 14,323 with 95% Cl = 3,278 - 55,028). While the dominant factors which influenced was not doing the ellimination of mosquitos nest OR = 14,323 with 95% Cl = 3,728-55,028 meant that someone who didnt eliminate mosquitos nest would have a risk 14 times greater to have the Filariasis compared with someone who eliminate teh mosquitos nest. From the research result it is better to elliminate the mosquitos nest by cleaning the water plants, filling the flooded area, cleaning the drain, flowing the flooded area, making the drain for garbage disposal, cleaning the bushes and not hanging teh dirty clothes.